(3GdehGgH GdfMhjI Ydi GdNdGUI hGdCdaGX GdHhfjIs - (3eMeO Hf CMeO GdZdGhj GdTfbjWj,J (B1288 (3g` s ((3CMeO Hf CMeO Hf GdaGVd s)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO ai PGJg hai CaYGdg CeG HYO adG Cf GdNdGUI ddEeGe eGdc CReI GdaVGFd GHf eGdc ef GdCdaGX GdHhfjI TQYJ ai GdTQM dLejY eG gfGdc hGdEjVGM , UfGekG Edi Pdc ef GdahGFO s
(3BNQgG (B:s
(3hefg bhdg JYGdi (B" (3EP jQjce Gdgd ai efGec bdjdkG (B" (3Ke bGd (B: " (3hef NGda ai JYOjgG Edi EKfjf LYd GdefUhH gfGdc hGdKGdK gfG MGdGf GfJgi GdLRA GdChd s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3MhGa HYV GdChQGb eJbUaIs
(3fSNI eUMMI s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdfMhs